Basal Gastric Acid level in Patients of Chronic Kidney Disease - Jafrin, Nilima; Akter, Nayeema; Akhter, Shahin; Mozumder, Md Myenuddin; Khan, Sakhawat Mahmud (Journal of Bangladesh Society of Physiologist, 2017)
Background: Gastrointestinal symptoms are common in patients with chronic kidney disease (CKD). Chronic renal failure is associated with an increased incidence of acid-related gastrointestinal disorders. Objective: To determine the pH level of gastric acid in patients of CKD and to correlate the different stages of CKD with gastric acid status. Methods: This study was carried out in the Department of Physiology and Nephrology, Chittagong Medical College and Hospital during January 2008 to December 2008. Total 87 subjects were included in this study, of them 65 patients of diagnosed case of chronic kidney diseases were selected as study group. Age and sex matched 22 apparently healthy persons were selected as control group To assess gastric juice media gastric juice pH level was determined with the help of Model pHs -25 pH meter. Data were analyzed by Chi-square test, Students t-test and Pearsons correlation co-efficient test where applicable. Results: Mean gastric juice pH level of CKD patients was lower than that of control group but it was not statistically significant. Again, pH level of gastric juice was significantly (p<0.001) decreased according to severity of CKD patients. Gradual decrease of pH level was found with the increasing severity of the CKD. Conclusion: In this study gastric juice pH was lowered in patients of chronic kidney disease which was significantly lowered in stage V. So it can be concluded that the gastric acid secretion may increase in chronic renal failure patient. Bangladesh Soc Physiol. 2017, June; 12(1): 10-14